Zero-valent iron biochar composite material capable of degrading tetracycline and preparation method of zero-valent iron biochar composite material
By preparing zero-valent iron-biochar composite materials from iron tailings and reed straw, and reacting with persulfate, the problems of low tetracycline pollutant removal efficiency and high zero-valent iron preparation cost in the existing technology are solved, and high efficiency is achieved. Degradation of tetracycline and resource recycling.
Patent Information
- Application Number
- CN202411789929.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-06
- Publication Date
- 2025-01-24
AI Technical Summary
The prior art is difficult to effectively remove contaminants from antibiotic drugs such as tetracycline, and the preparation cost of zero-valent iron is high, which limits its practical application.
By using iron tail mines and reed straw as raw materials, the iron and alkaline precipitation process are deposited on the surface of the reed straw, and then a thermal solution reaction is performed to form zero-valence iron-biological carbon composite materials and react with excessive sulfate reactions to excessive sulfate reactions , Generate high -active free radicals for tetracycline degradation.
The collaborative resource utilization of iron tailings and reed straw is achieved, the preparation cost of zero-valent iron is reduced, and the degradation efficiency of tetracycline is improved. The degradation rate reaches 81.85%, and it is in line with the concept of circular economy.
Smart Images

Figure CN119346068A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of environmental protection and resource recycling, and in particular to a zero-valent iron biochar composite material capable of degrading tetracycline and a preparation method thereof. Background Art
[0002] In recent years, antibiotics (such as tetracycline) have been widely used in the fields of medicine, animal husbandry and aquaculture, resulting in a large amount of their residues discharged into water bodies. Due to the high stability, difficulty in degradation and potential biological toxicity of antibiotics, they exist in the environment for a long time, affecting the balance of aquatic ecosystems and posing a threat to human health through the food chain. In addition, the abuse and residues of antibiotics can also induce bacterial resistance, making the spread of drug-resistant pathogens a major challenge to global public health. Existing sewage treatment processes, such as conventional biodegradation and chemical oxidation, are difficult to effectively remove these antibiotic pollutants. Therefore, the development of efficient and environmentally friendly removal technologies has become an urgent need for water pollution control.
[0003] In recent years, advanced oxidation technology has gradually entered the public eye due to its high efficiency and no secondary pollution. Among them, the zero-valent iron activated persulfate process is widely used in water pollution control due to its excellent reduction performance and environmental compatibility. Zero-valent iron activated persulfate produces strong oxidizing free radicals that reduce a variety of pollutants into non-toxic or low-toxic substances, which is particularly suitable for treating difficult-to-degrade organic pollutants and heavy metal ions. However, in practical applications, zero-valent iron is prone to agglomeration and surface passivation, resulting in a decrease in specific surface area and reduced reaction activity. Loading zero-valent iron on porous materials such as biochar can effectively solve these problems. Biochar not only provides a good dispersion medium to prevent particle agglomeration, but also has excellent adsorption capacity, which synergizes with zero-valent iron to further improve the removal efficiency of pollutants.
[0004] However, a large amount of iron raw materials are needed in the preparation process of zero-valent iron, and its preparation cost further limits its practical application. Iron tailings are by-products produced during mining and smelting, containing a certain amount of iron and other mineral components. Due to its huge emission, if it is not treated and stored, it will not only occupy land resources, but may also cause soil and groundwater pollution. Based on this, the inventor considered using iron ore to prepare zero-valent iron biochar composite materials, aiming to achieve resource recycling while reducing the preparation cost of zero-valent iron. Summary of the invention
[0005] The present invention aims to provide a zero-valent iron biochar composite material capable of degrading tetracycline and a preparation method thereof, so as to solve the problems of resource waste and high cost of preparing zero-valent iron in the prior art.
[0006] To achieve the above-mentioned purpose, the present invention adopts the following technical scheme: a zero-valent iron biochar composite material capable of degrading tetracycline is prepared by pyrolysis reaction using iron tailings and reed straw as raw materials, and the mass ratio of iron tailings to reed straw is 0.8 to 1:1.
[0007] Preferably, as an improvement, the iron tailings are pre-treated by acid leaching.
[0008] Preferably, as an improvement, the acid reagent for acid leaching pretreatment is hydrochloric acid, the concentration of the hydrochloric acid is 4-6M, and the leaching temperature is 80°C.
[0009] Preferably, as an improvement, the pyrolysis reaction is anaerobic pyrolysis, the pyrolysis temperature is 800-850° C., and the pyrolysis time is 2-2.5 h.
[0010] Preferably, as an improvement, a method for preparing a zero-valent iron biochar composite material capable of degrading tetracycline comprises the following steps:
[0011] Step 1: pretreatment of iron tailings: mixing the iron tailings with a hydrochloric acid solution, heating in a water bath for leaching treatment, so that the iron components contained therein are fully leached to obtain an iron-rich solution;
[0012] Step 2: Loading iron on reed straw: Mix the reed straw with the iron-rich solution obtained in step 1, and add an alkali treatment agent dropwise until precipitation is complete and continue stirring;
[0013] Step 3: Pyrolysis reaction: Pyrolyze the iron-loaded reed straw in an anaerobic environment to prepare a zero-valent iron-biochar composite material.
[0014] Preferably, as an improvement, in step 2, the alkaline treatment agent is a sodium hydroxide solution, the concentration of the sodium hydroxide solution is 4-6M, and the continuous stirring time is 2h.
[0015] Preferably, as an improvement, in step 2, after stirring, the iron-loaded reed straw is filtered and then dried.
[0016] Preferably, as an improvement, the method further comprises step 4, degradation reaction: adding the biochar obtained in step 3 together with persulfate into the tetracycline solution and stirring for reaction.
[0017] Preferably, as an improvement, in step 4, the persulfate is potassium persulfate, the mass concentration of potassium persulfate is 0.2-0.4%, and the stirring reaction time is 1 hour.
[0018] Preferably, as an improvement, in step 4, the amount of biochar added to the reaction system is 0.5-0.7 g / L.
[0019] The principle and advantages of this scheme are as follows: In actual application, this technical scheme deposits the iron in the iron tailings on the surface of reed straw through acid leaching and alkali precipitation processes, and uses organic components such as cellulose and hemicellulose in the straw as carbon sources during pyrolysis to reduce iron oxide to zero-valent iron, forming a zero-valent iron-biochar composite material. During the application process, the zero-valent iron loaded on the biochar reacts with persulfate to activate and generate sulfate radicals (SO4 - ·) and hydroxyl radicals (·OH), these highly active free radicals can quickly decompose organic pollutants such as tetracycline, degrading them into harmless small molecules, and realizing efficient treatment of water pollution. In the technical research and development stage, how to achieve sufficient leaching of iron elements in tailings is one of the research and development difficulties of this technical solution. The inventor of this solution has conducted research on the acid leaching process, and has obtained the optimal leaching effect by conducting targeted research on the types of acids and the ratios with tailings. In addition, in the process of preparing biochar composite materials, the inventors have also tried to prepare biochar from iron tailings and humic acid waste (weathered coal) and protein waste (beer grains), but the results were not ideal. When using iron tailings and reed waste to prepare biochar, the inventors optimized the tailings dosage and pyrolysis conditions so that the prepared biochar has excellent adsorption and degradation properties.
[0020] In summary, the present invention realizes the coordinated resource utilization of wastes such as iron tailings and reed straw, reduces the cost of material preparation, and conforms to the concept of circular economy. The combination of zero-valent iron and biochar improves the performance of the material. The adsorption of biochar enhances the contact between pollutants and zero-valent iron, while the reducibility of zero-valent iron enhances the activation effect of persulfate, so that pollutants can be rapidly degraded. According to the experimental results, the zero-valent iron-biochar composite material prepared by this process scheme based on iron tailings and reed straw shows excellent degradation performance for tetracycline by activating persulfate. Under the addition of 0.2% persulfate system and 0.5g / L biochar material, the degradation rate of 200mg / L tetracycline reaches 81.85%. The whole process is simple, environmentally friendly, and easy to promote. It is not only suitable for the degradation of tetracycline, but also can be widely used in the treatment of other organic pollutants and heavy metal pollution, with significant environmental, economic and social benefits. BRIEF DESCRIPTION OF THE DRAWINGS
[0021] Figure 1 This is a flow chart of the synergistic preparation of biochar using iron tailings and reed straw in an embodiment of the present invention. DETAILED DESCRIPTION
[0022] The following is further described in detail through specific implementations, but the implementation of the present invention is not limited thereto. Unless otherwise specified, the technical means used in the following implementations are conventional means well known to those skilled in the art; the experimental methods used are all conventional methods; the materials, reagents, etc. used can all be obtained from commercial channels.
[0023] Program Overview:
[0024] A zero-valent iron biochar composite material capable of degrading tetracycline is prepared by taking iron tailings and reed straw as raw materials through a pyrolysis reaction, wherein the mass ratio of the iron tailings to the reed straw is 0.8-1:1.
[0025] like Figure 1 As shown: A method for preparing a zero-valent iron biochar composite material capable of degrading tetracycline comprises the following steps:
[0026] Step 1: pretreatment of iron tailings: mixing the iron tailings with a hydrochloric acid solution, heating in a water bath for leaching treatment, so that the iron component contained therein is fully leached to obtain an iron-rich solution; the concentration of the hydrochloric acid is 4-6M, the leaching temperature is 80°C, and the leaching time is 2h;
[0027] Step 2: Loading iron on reed straw: fully mix the reed straw with the iron-rich solution obtained in step 1, add 4-6M alkaline precipitant (sodium hydroxide solution) dropwise until precipitation is complete and stir for 2 hours, then filter through a 0.45um filter membrane to obtain iron-loaded reed straw, and dry at 65°C;
[0028] Step 3, pyrolysis reaction: pyrolyzing the iron-loaded reed straw in an anaerobic environment to prepare a zero-valent iron-biochar composite material; the pyrolysis method is anaerobic pyrolysis, the pyrolysis temperature is 800-850° C., and the pyrolysis time is 2-2.5 h;
[0029] Step 4, degradation reaction: add the biochar obtained in step 3 together with potassium persulfate into the tetracycline solution and stir to react for 1 hour; the mass concentration of potassium persulfate is 0.2-0.4%, and the amount of biochar added to the reaction system is 0.5-0.7 g / L.
[0030] Example 1
[0031] A process for preparing a zero-valent iron-biochar composite material for degrading tetracycline by synergistically using iron tailings and reed straw comprises the following steps:
[0032] Step 1: Pretreatment of iron tailings: 4 g of iron tailings were mixed with 20 ml of 5 M hydrochloric acid solution, and heated in a water bath at 80° C. for 2 h for leaching, so that the iron components contained therein were fully leached;
[0033] Step 2: Reed straw loaded with iron: Weigh 5 g of reed straw and mix it thoroughly with the iron-rich solution obtained in step 1, add 5M sodium hydroxide solution dropwise until precipitation is complete and continue stirring for 2 hours; filter through a 0.45 um filter membrane to obtain the iron-loaded reed straw, and dry it at 65°C;
[0034] Step 3, pyrolysis reaction: pyrolyzing the iron-loaded reed straw in an anaerobic environment at a pyrolysis temperature of 800° C. for 2 h to prepare a zero-valent iron-biochar composite material;
[0035] Step 4: Degradation reaction: Add the biochar obtained in step 3 and potassium persulfate into a 200 mg / L tetracycline solution, with a biochar dosage of 0.5 g / L and a persulfate concentration of 0.2%, and stir to react for 1 hour.
[0036] Comparative Example 1
[0037] The difference between this comparative example and Example 1 is that in this comparative example, in step 1, the amount of iron tailings added is 2 g, that is, the mass ratio of iron tailings to reed straw is 0.4:1.
[0038] Comparative Example 2
[0039] The difference between this comparative example and Example 1 is that in this comparative example, in step 1, the leaching solution is H2SO4.
[0040] Comparative Example 3
[0041] The difference between this comparative example and Example 1 is that in this comparative example, in step 1, the acid concentration is 2.5M.
[0042] Comparative Example 4
[0043] The difference between this comparative example and Example 1 is that in this comparative example, in step 1, the water bath temperature is 50°C.
[0044] Comparative Example 5
[0045] The difference between this comparative example and Example 1 is that in this comparative example, in step 3, the pyrolysis temperature is 500°C.
[0046] Comparative Example 6
[0047] The difference between this comparative example and Example 1 is that in this comparative example, in step 4, the concentration of persulfate is 0.1%.
[0048] Comparative Example 7
[0049] The difference between this comparative example and Example 1 is that in this comparative example, in step 4, the amount of zero-valent iron-biochar used is 0.3 g / L.
[0050] Comparative Example 8
[0051] The difference between this comparative example and Example 1 is that in this comparative example, in step 1, the amount of iron tailings added is 5 g.
[0052] Comparative Example 9
[0053] The difference between this comparative example and Example 1 is that in this comparative example, in step 2, the waste biomass is replaced by an equal amount of weathered coal in place of reed straw.
[0054] Comparative Example 10
[0055] The difference between this comparative example and Example 1 is that in this comparative example, in step 2, the waste biomass is replaced by an equal amount of brewer's grains instead of reed straw.
[0056] Experimental Example 1 Tetracycline Degradation Efficiency Test
[0057] The tetracycline degradation efficiency of Example 1 and Comparative Examples 1 to 7 was tested, and the calculation formula is shown in formula (1):
[0058]
[0059] Where C0 and C e (mg / L) are the initial concentration of tetracycline and the concentration when the reaction is complete.
[0060] The test results are shown in Table 1: The results show that under the experimental conditions, the degradation rate of tetracycline by biochar activated persulfate reached a maximum of 81.85%. When the leaching conditions such as the type of leaching agent (sulfuric acid), concentration and water bath temperature were changed, the iron extraction efficiency of the iron tailings was low, resulting in insufficient iron loaded on the reed straw, and the subsequent biochar surface loaded with zero-valent iron was insufficient, and the degradation rate of tetracycline was reduced at this time; in terms of biomass type and amount, the ratio of biomass to tailings was 1:1, which also led to a decrease in the adsorption performance of the prepared biochar; replacing the biomass with an equal amount of humic acid waste or an equal amount of protein waste, the degradation rate of tetracycline by the prepared biochar was only about 60%; in addition, under the lower pyrolysis conditions of 500°C, the reduction of iron to zero-valent iron was insufficient, which also led to a decrease in the degradation effect of tetracycline. In the persulfate system, changing the persulfate concentration and biochar dosage also had a negative impact on tetracycline degradation. Only when the persulfate concentration was 0.2% and the biochar dosage was 0.5 g / L, the tetracycline degradation rate reached the optimal level of 81.85%.
[0061] Table 1
[0062]
[0063] The above is only an embodiment of the present invention, and the common knowledge such as the known specific technical solutions and / or characteristics in the solution is not described in detail here. It should be pointed out that for those skilled in the art, without departing from the technical solution of the present invention, several modifications and improvements can be made, which should also be regarded as the protection scope of the present invention, and these will not affect the effect of the implementation of the present invention and the practicality of the patent. The scope of protection required by this application shall be based on the content of its claims, and the specific implementation methods and other records in the specification can be used to interpret the content of the claims.
Claims
1. A zero-valent iron biochar composite material capable of degrading tetracycline, characterized in that: The product is prepared by taking iron tailings and reed straw as raw materials through pyrolysis reaction, and the mass ratio of the iron tailings to the reed straw is 0.8-1:
1.
2. The zero-valent iron biochar composite material capable of degrading tetracycline according to claim 1, characterized in that: The iron tailings are pre-treated by acid leaching.
3. The zero-valent iron biochar composite material capable of degrading tetracycline according to claim 2, characterized in that: The acid reagent for acid leaching pretreatment is hydrochloric acid, the concentration of hydrochloric acid is 4-6M, and the leaching temperature is 80°C.
4. The zero-valent iron biochar composite material capable of degrading tetracycline according to claim 3, characterized in that: The pyrolysis reaction is anaerobic pyrolysis, the pyrolysis temperature is 800-850° C., and the pyrolysis time is 2-2.5 hours.
5. The method for preparing a zero-valent iron biochar composite material capable of degrading tetracycline according to any one of claims 1 to 4, characterized in that: The steps include: Step 1: pretreatment of iron tailings: mixing the iron tailings with a hydrochloric acid solution, heating in a water bath for leaching treatment, so that the iron components contained therein are fully leached to obtain an iron-rich solution; Step 2: Loading iron on reed straw: Mix the reed straw with the iron-rich solution obtained in step 1, and add an alkali treatment agent dropwise until precipitation is complete and continue stirring; Step 3: Pyrolysis reaction: Pyrolyze the iron-loaded reed straw in an anaerobic environment to prepare a zero-valent iron-biochar composite material.
6. The method for preparing a zero-valent iron biochar composite material capable of degrading tetracycline according to claim 5, characterized in that: In step 2, the alkaline treatment agent is a sodium hydroxide solution, the concentration of the sodium hydroxide solution is 4-6M, and the continuous stirring time is 2h.
7. The method for preparing a zero-valent iron biochar composite material capable of degrading tetracycline according to claim 6, characterized in that: In step 2, after stirring, the iron-loaded reed straw is filtered and then dried.
8. The method for preparing a zero-valent iron biochar composite material capable of degrading tetracycline according to claim 7, characterized in that: The method further comprises step 4, degradation reaction: adding the biochar obtained in step 3 together with persulfate into the tetracycline solution and stirring for reaction.
9. The method for preparing a zero-valent iron biochar composite material capable of degrading tetracycline according to claim 8, characterized in that: In step 4, the persulfate is potassium persulfate, the mass concentration of potassium persulfate is 0.2-0.4%, and the stirring reaction time is 1 hour.
10. The method for preparing a zero-valent iron biochar composite material capable of degrading tetracycline according to claim 9, characterized in that: In step 4, the amount of biochar added to the reaction system is 0.5-0.7 g / L.
Citation Information
Cited By
Iron-carbon filler as well as preparation method and application thereof
CN120664655A